Influence of temperature and mango pulp thickness on the performance of batch window refractance dryer - Samrawit Kasse Gebeyehu; Aynadis Molla Asemu; Abiy Solomon Haile; Messenbet Geremew Kassa (Applied Food Research)
Fruits and vegetables are highly perishable, with significant post-harvest losses in countries like Ethiopia due to limited processing. Drying is a widely used preservation method that reduces moisture content and extends the shelf life of these products. In this study, the drying performance of the relatively new Batch Window Refractance Dryer (BWRD) was evaluated using various drying temperatures (75, 85, and 95°C) and mango pulp thicknesses (1, 3, and 5 mm). The study examined the dryer’s overall energy efficiency, as well as the drying kinetics and behavior of mango pulp, using thin-layer drying models and Fick’s law of diffusion. Results showed that drying occurred in the falling rate period for all treatments, with the Page model best fitting the drying kinetics. The effective moisture diffusivity (Deff) of mango pulp increased with both pulp thickness and drying temperature, averaging 6.31 × 10⁻¹³, 8.64 × 10⁻¹³, and 17.68 × 10⁻¹³ m²/s for thicknesses of 1 mm, 3 mm, and 5 mm, respectively. Similarly, Deff increased with higher drying temperatures, showing values of 4.18 × 10⁻¹³, 11.27 x 10⁻¹³, and 17.18 × 10⁻¹³ m²/s at drying temperatures of 75°C, 85°C, and 95°C, respectively. The activation energy (Ea) for drying mango pulp increased with thickness, measured at 46.179 kJ/mol for 1 mm, 49.49 kJ/mol for 3 mm, and 57.481 kJ/mol for 5 mm. The dryer’s energy efficiency for drying 1 kg of mango pulp varied with thickness, yielding efficiencies of 62.64 % ± 12.37 for 1 mm, 32.57 % ± 6.75 for 3 mm, and 24.29 % ± 6.37 for 5 mm. The results show that as drying temperature and mango pulp thickness increase, energy consumption rises and energy efficiency decreases, with these effects being statistically significant (P < 0.05).This highlights the impact of thickness and drying temperature on the energy efficiency of the drying process.